COVID-19 living evidence profile #2 (version 2.2): What is known about preventing and managing COVID-19, outbreaks of COVID-19, and about supporting renewal in long-term care homes? - Waddell, K; DeMaio, P; Wilson, MG; Bain, T; Wang, Q; Al-Khateeb, S; Alam, S; Sharma, K; Whitelaw, S; Gauvin, François-Pierre; Lavis, JN (My University, 2021)
An overview of the best available research evidence from around the world (i.e., evidence syntheses) and local research evidence (i.e., single studies) and, if applicable, a scan of experiences from other countries and from Canadian provinces and territories, about preventing and managing COVID-19, outbreaks of COVID-19, and about supporting renewal in long-term care homes in response to a decision-maker’s request.
Keywords: prevention; management; COVID-19; outbreaks; renewal; long-term care